Answer:
The quadratic function is: [tex](x-2)(x-12)=0[/tex] and can be written as: [tex]x^2-14x+24=0[/tex]
Step-by-step explanation:
A quadratic function can typically be written in multiple forms, among which includes: (x-a)*(x-b)=0 where a, b can be any number
This quadratic function is solved for a and b, which represents the zeroes (or can be called roots) of the equation.
Given that the zeroes are already given, all that's need to write the quadratic function is to substitute a and b with the given zeroes:
Note: It doesn't matter which zeroes are substituted for a and b
(x-a)*(x-b)=0
(x-2)*(x-12)=0
Now, we can leave it in this form or expand the equation (often called the FOIL method):
(x-2)*(x-12)=0 Multiply each term with the other terms
[tex]x^2-2x-12x+24=0[/tex] Simplify by combining like terms
[tex]x^2-14x+24=0[/tex]
Thus, the quadratic function for zeroes 12 and 2 is: [tex]x^2-14x+24=0[/tex]